CALL OF PROSPERITY: FARMERS’ ATTITUDE AND SUCCESS FROM THE KISAN CALL CENTRE IN ASSAM - NIBIR PRATIM CHOUDHURY; AMIT CHOUDHURY (The Journal of Research ANGRAU, 2024)
In an effort to close the gap between the needs of farmers and the distribution of agricultural information, this study examines how farmers perceive the advice offered by Kisan Call Centres (KCCs). KCCs are vital sources that provide knowledge on different farming techniques, professional counsel, and agricultural guidance. However, enhancing the efficacy of agricultural extension services requires an understanding of how farmers interpret and apply these advisories. The study uses a mixed-methods approach, including surveys and in-depth interviews with 100 farmers from the State of Assam, representing a heterogeneous sample. The findings show a range of opinions, impacted by variables viz., age, education, landholding, experience and annual income. The study shows 41 % of respondents were under 30 years old, with 68 % depending on farming and 61 % holding 7.6-15 bighas of land. Farmers appreciated KCC’s quick responses, especially for weather forecasts, but noted issues with insufficient information, pest symptom descriptions, and long wait times. Age, experience, landholding, and income positively correlated with favourable attitudes towards KCC, while education had a negative impact.